Pengaruh Live Streaming Tiktok terhadap Minat Beli Skincare Somethinc melalui Kepercayaan Konsumen pada Mahasiswa Manajemen Universitas Negeri Makassar - Gaby Putri Edy; Agung Widhi Kurniawan; Muhammad Ichwan Musa; Muhammad Ilham Wardhana Haeruddin; Nurul Fadilah Aswar (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
The rapid growth of social commerce has encouraged skincare brands to use TikTok live streaming as an interactive marketing strategy to attract digital consumers. Somethinc, as a local skincare brand, actively utilizes TikTok live streaming to present product information, promotions, and real-time interaction with potential buyers. This study aims to analyze the effect of TikTok live streaming on purchase intention for Somethinc skincare products through consumer trust as an intervening variable among Management students at Universitas Negeri Makassar. This research used a quantitative approach with a causal design. Data were collected through online questionnaires distributed to 120 respondents selected using purposive sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS 4. The results show that TikTok live streaming has a positive and significant effect on purchase intention, while consumer trust also has a positive and significant effect on purchase intention. However, TikTok live streaming does not significantly affect consumer trust, and consumer trust does not mediate the relationship between TikTok live streaming and purchase intention. These findings indicate that TikTok live streaming directly encourages purchase intention through interactive product presentation, real-time communication, and promotional appeal, rather than through the formation of consumer trust. The study implies that Somethinc should optimize live streaming content while strengthening trust through authentic reviews, transparent product information, and safety assurance.